Promoting the Character of Respect for Each Other through the Pancasila Student Profile Strengthening Project (P5): Educational Transformation in the Merdeka Curriculum Era - Alhamuddin Alhamuddin; Andi Murniati (UPT Publikasi Ilmiah UNISBA, 2024)
This study aims to analyze how the P5 in Merdeka Curriculum can strengthen students' mutual respect character. Using a qualitative approach based on documentation studies, this research examines curriculum documents, learning modules, project implementation reports, student reflections, and school evaluations to understand the implementation of P5 in depth. The results show that P5, through themes such as Local Wisdom and Unity in Diversity, provides opportunities for students to learn to recognize and appreciate diversity. Heterogeneous group-based projects are an effective medium in training students to collaborate, understand differences, and resolve conflicts constructively. Students' reflections showed positive changes in the way they viewed cultural and social differences. However, this study also found that the successful implementation of P5 is influenced by teacher readiness, resource availability, and educational policy support. The conclusion of this study is that P5 has great potential in shaping students' respectful character if implemented with adequate support. It is recommended that schools improve teacher training, provide supporting facilities, and allocate sufficient time for project implementation. These interventions are important to ensure that the positive impact of P5 can be felt equally by all students.